The world of the polis: reflections on the Athenian model and the crisis in the territory of the poleis in the fourth century BC - André, Alessandra (Romanitas - Revista de Estudos Grecolatinos, 2016)
Derived from the Greek word polis, meaning city, the adjective poliade, used to describe the political system that emerged in Greece around the eighth century BC, defines the territory that became known as Hellas, and entered into a process of disintegration from the end of the fifth century BC. Our goal in this article is to outline in general terms the nature of this particular type of state which was the Greek city at the same time we seek to examine the elements that led to the breakdown of this system, as the Peloponnesian War and the rise of Macedonia as a political and military power, factors that contributed in some way for further reflection on polis and basileia. Because most of the information about the Greek politeia comes from Athens and the sources consulted in this work are of Athenian origin, we develop our reflections based on such polis.